MEMS Packaging Technologies and 3D Integration - Seok, Seonho (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue introduces recent research results on MEMS packaging and 3D integration whose subjects can be divided as follow; three papers on biocompatible implantable packaging, three papers on interconnect, three papers on bonding technologies, one paper on vacuum packaging, and three papers on modeling and simulation.